Microsurgical Replantation of Total Avulsed Scalp: Extending the Limits. Issue 3 (May 2017) - Jin, Yunbo; Hua, Chen; Hu, Xiaojie; Chen, Hui; Ma, Gang; Zou, Yun; Chen, Bin; Lyu, Dongze; Tremp, Mathias; Lin, Xiaoxi
Abstract : Background: Avulsion of the scalp is a rare but severe trauma and challenging to the reconstructive surgeon. It poses not only physical concussion but also significant persisting psychological distress to the patients. Methods: Medical records from 5 patients who suffered scalp avulsion were reviewed retrospectively. The following data and methods were assessed: age, number of vessels repaired, method of replantation, vein grafts required, blood transfusion, ischemia time, total operating time, and percentage of scalp survival. Results: In 4 patients, the replantation was performed at the anatomic site. Two arteries and 2 veins were anastomosed in 2 patients; a single artery and a single vein were anastomosed in 2 patients. The middle temporal vein was chosen for anastomosis as a recipient vessel in 2 patients. In the fifth patient with simultaneous cervical fracture that makes primarily replantation technically not possible, the scalp was implanted ectopically in the forearm for the purpose of secondary replantation at the anatomic site. After a mean follow-up of 22.6 months (range 13–29 months), 4 of 5 patients exhibited successful survival of the replanted scalp. Conclusions: The success of scalp replantation is determined by a comprehensive management of the trauma and well-trained microsurgical technique. The middle temporal vein can be used as a reliable alternative recipient vessel for microvascular anastomosis when replanting the avulsed scalp. In patients in whom primary replantation is not possible, temporary ectopic implantation of the avulsed scalp and anatomic replantation at a second stage is considerable.